Analysis of Matrix Converter as Solid State Transformer (SST) in Battery Charging Using Fuzzy Logic Control - Lungguk Sibuea (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
Technological advancements in the digital era have made electrical energy needs vital in the industrial world. The reliability of electricity supply certainly has serious challenges related to transmission system blackouts due to the failure of blackstart at the plant because the battery supply is not functioning optimally. To anticipate this failure, Matrix Converter (MC) modeling is carried out as a Solid State Transformer (SST) to replace conventional transformers to maintain voltage stability and change the voltage according to the needs for battery supply. The SVPWM methodology uses 9 bidirectional switches in the MC to modulate pulse width by comparing the duty cycle against high-frequency waves. This comparison can determine when each switch in the converter should be open or closed in each switching cycle. To control stable voltage and efficient current in the battery charging process, Fuzzy Logic control (FLC) is used. With a Rectifier as the converter (AC-DC), a stable voltage of 127.6 volts DC is obtained, so the battery charging process can work optimally and stably.